Editorial - Yuktanandana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery, volume 41 no. 3-4, has been launched during the RCOST meeting on the 20th to the 22nd October 2017 at Pattaya Exhibition and Convention Hall, Royal Cliff Hotels Group. This year is another very special, as we are preparing for the Royal Cremation of the beloved King Bhumibol Adulyadej on the 26th of October 2017. Nevertheless, our academic meeting of the Royal College of Orthopaedic Surgeons of Thailand, under the patronage of King Bhumibol Adulyadej, is aimed to exchange knowledge among orthopaedic surgeons by the theme “Wisdom comes with healthy ageing”. The Royal College also arranges social events for the unity of our members, who devoted themselves helping people around the country. This year, we have 3 members who will receive 3 awards, one for best service, one for best management and another for best academic progression. I would like to congratulate to all of their successes. This volume consisted of various topic from trauma, spine and arthroplasty sections. The comparison of quality of life between fixation and arthroplasty in intertrochanteric fracture of femur in elderly patients by Yodsawee Pornmeechai. This research showed that the short term quality of life in arthroplasty group was higher than fixation group, but the incidence of mortality in both groups were as high as 25-38 percent after one year. Chote Pawasuttikul showed in his article that there was no function different between one or two levels fusion with pedicular screw fixation for single level spondylolisthesis of lumbar spines after 5 years follow up period. There were two cases reports in the treatment of difficult knee osteoarthritis with severe genu recurvatum by Kulapat Chulsomlee. The successful surgical treatment were done by using rotating hinge knee prosthesis which is a very interesting procedures. Another basic research is the estimation of Inter Iliac crest distance by ulna length measurement for reference in reduction of pelvic fractures by Satapong Pisuitthanakan. It is also interesting but the result was not yield good correlation. I hope that the Thai Journal of Orthopaedic Surgery is a very useful ground for academic publication of our members and friends from ASEAN countries. The acceptance of our journal will be higher by the contribution of our members. Please submit your research in our journal.